The crosstalk between DRP1-dependent mitochondrial fission and oxidative stress triggers hepatocyte apoptosis induced by silver nanoparticles. Issue 28 (13th July 2021) - Li, Jiangyan; Chang, Xiaoru; Shang, Mengting; Niu, Shuyan; Zhang, Wenli; Li, Yunjing; Sun, Zuoyi; Wu, Tianshu; Kong, Lu; Zhang, Ting; Tang, Meng; Xue, Yuying
Abstract : Previous studies have revealed that the liver is the main target organ of deposition for engineered nanoparticles. Abstract : Previous studies have revealed that the liver is the main target organ of deposition for engineered nanoparticles. The hepatotoxicity of silver nanoparticles (AgNPs), the widely used antimicrobial nanoparticles, has been of great interest. However, little is known about the regulatory mechanism of the mitochondria in AgNP-induced hepatotoxicity. In the present study, we found that AgNPs, rather than silver ions, induced mitochondrial dynamics disorders, oxidative stress, and mitochondria-dependent hepatocyte apoptosis in mice. Using human hepatocellular carcinoma (HepG2) cells, we confirmed that the interaction between dynamin-related protein 1 (DRP1)-dependent mitochondrial fission and oxidative stress promoted mitochondrial damage and mitochondria-dependent apoptosis induced by AgNPs, as determined by the elimination of DRP1 or addition of N -acetylcysteine (NAC). Interestingly, the crosstalk between DRP1-dependent mitochondrial fission and oxidative stress also activated mitophagy and autophagy flux blocking. Phosphatase and tensin homolog (PTEN)-induced putative kinase 1 (PINK1) gene silencing contributed to the aggravation of mitochondrial damage, oxidative stress, and apoptosis. These results revealed that the interplay between mitochondrial fission and oxidative stress induced mitophagy defects and triggered AgNP-induced mitochondria-dependent apoptosis in liver cells both in vivo and in vitro . Our findings provide a perspective for the mechanism of hepatotoxicity induced by exposure to metal NPs.